A Silent Epidemic: The Prevalence, Incidence and Persistence of Mycoplasma genitalium Among Young, Asymptomatic High-Risk Women in the United States - Seña, Arlene C (Clin Infect Dis, 2018)
BACKGROUND: Mycoplasma genitalium can result in pelvic inflammatory disease and adverse pregnancy outcomes. We analyzed data collected from a prospective study of asymptomatic bacterial vaginosis (BV) to determine the natural history of M. genitalium. METHODS: Women aged 15–25 years, with asymptomatic BV and ≥2 risk factors for sexually transmitted infection were recruited from 10 sites throughout the United States. Vaginal swab samples were collected at enrollment and through home-based testing every 2 months over 12 months. M. genitalium nucleic acid amplification testing was performed for M. genitalium using transcription-mediated assays (Hologic). The prevalence, incidence, and persistence of M. genitalium, defined as all positive specimens during follow-up, were estimated with 95% confidence intervals (CIs). Adjusted odds ratios (AOR) were calculated using logistic and Poisson regression to evaluate participant characteristics associated with M. genitalium infection. RESULTS: Among 1139 women, 233 were M. genitalium positive, for a prevalence of 20.5% (95% CI, 18.2%–22.9%); 42 of 204 had persistent M. genitalium (20.6%). Among 801 M. genitalium–negative women at baseline, the M. genitalium incidence was 36.6 per 100 person-years (95% CI, 32.4–41.3). Black race (AOR, 1.92; 95% CI, 1.09–3.38), age ≤21 years (1.40; 1.03–1.91), and prior pregnancy (1.36; 1.00–1.85) were associated with prevalent M. genitalium; only black race was associated with incident M. genitalium (P = .03). CONCLUSIONS: We identified high rates of prevalent, incident, and persistent M. genitalium infections among young, high-risk women with asymptomatic BV, supporting the need for clinical trials to evaluate the impact of M. genitalium screening on female reproductive health outcomes.